2002
DOI: 10.1016/s0893-133x(02)00373-1
|View full text |Cite
|
Sign up to set email alerts
|

Dextroamphetamine Modulates the Response of the Human Amygdala

Abstract: Amphetamine, a potent monoaminergic agonist, has pronounced effects on emotional behavior in humans, including the generation of fear and anxiety. Recent animal studies have demonstrated the importance of monoamines, especially dopamine, in modulating the response of the amygdala, a key brain region involved in the perception of fearful and threatening stimuli, and the generation of appropriate physiological and behavioral responses. We have explored the possibility that the anxiogenic effect of amphetamine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
115
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 26 publications
13
115
0
Order By: Relevance
“…As all of our subjects were cleared of medical or psychiatric disease or treatment, the two genotype groups did not differ on these parameters either. Furthermore, the two groups did not differ in 5-HTTLPR genotype status (w 2 ¼ 0.004, P ¼ 0.95), hTPH2 effects on amygdala reactivity Consistent with prior studies using this amygdala reactivity paradigm, 13,[22][23][24] analysis of the fMRI data revealed significant bilateral amygdala activation in all subjects. Direct genotype group comparisons revealed greater activity in the bilateral dorsal amygdala of hTPH2 T allele carriers in comparison with G allele homozygotes (Figure 1, Table 1).…”
Section: Sample Demographicssupporting
confidence: 84%
“…As all of our subjects were cleared of medical or psychiatric disease or treatment, the two genotype groups did not differ on these parameters either. Furthermore, the two groups did not differ in 5-HTTLPR genotype status (w 2 ¼ 0.004, P ¼ 0.95), hTPH2 effects on amygdala reactivity Consistent with prior studies using this amygdala reactivity paradigm, 13,[22][23][24] analysis of the fMRI data revealed significant bilateral amygdala activation in all subjects. Direct genotype group comparisons revealed greater activity in the bilateral dorsal amygdala of hTPH2 T allele carriers in comparison with G allele homozygotes (Figure 1, Table 1).…”
Section: Sample Demographicssupporting
confidence: 84%
“…27,39,57 Moreover, DA potentiates the response of the amygdala by attenuating the effect of inhibitory input from the PFC and by augmenting the effect of excitatory input from sensory cortices. 58 Consistent with this, fMRI studies in humans showed that DA modulates the responsivity of the amygdala to emotional stimuli, 59,60 and that COMT Val 158 Met affects DA synthesis in midbrain. 61,62 The potentiated amygdala response in carriers of the Met 158 alleles may thus reflect DA gating of amygdala inputs.…”
Section: Discussionmentioning
confidence: 76%
“…This paradigm has been used previously to investigate drug effects on amygdala reactivity. 26,27 It robustly engages the amygdala, by contrasting the response to simultaneously presented angry and fearful face stimuli (http:// www.macbrain.org) with the response to ellipses (that consisted of scrambles of the same face stimuli). The results therefore do not show emotion-specific effects, but rather a general response to salient, biologically relevant stimuli.…”
Section: Behavioral Taskmentioning
confidence: 99%